2015
DOI: 10.1039/c4dt02689f
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic C-nitrosation by a copper(ii)–nitrosyl complex

Abstract: Copper(II) complex of 4-amino-3-hydroxy-1-sulphonic acid was synthesized and characterized. Upon addition of nitric oxide, the copper(II) center of the complex in methanol was found to undergo reduction through an unstable copper(II)-nitrosyl intermediate. The formation of the intermediate was confirmed by UV-visible and FT-IR spectroscopy. The reduction of the copper(II) center was accompanied with a simultaneous C-nitrosation of the aromatic ring of the ligand. The C-nitrosation product was isolated and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…First, a broad band at 1651 cm −1 was observed after NO exposure and was irreversible after purging with N 2 . 97 This band was assigned to NO binding to Cu centers or NO reacting with organic protons of the framework to form R-NO nitroso compounds. Second, a series of bands (1585, 1261, 1039, 917, and 833 cm −1 ) (Figure S54) indicated the presence of more oxidized nitrate species most likely adsorbed in a variety of bidentate configurations to Cu centers (Figure 6G).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a broad band at 1651 cm −1 was observed after NO exposure and was irreversible after purging with N 2 . 97 This band was assigned to NO binding to Cu centers or NO reacting with organic protons of the framework to form R-NO nitroso compounds. Second, a series of bands (1585, 1261, 1039, 917, and 833 cm −1 ) (Figure S54) indicated the presence of more oxidized nitrate species most likely adsorbed in a variety of bidentate configurations to Cu centers (Figure 6G).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Difference spectra revealed three key spectroscopic features upon exposure to NO and subsequent purging. First, a broad band at 1651 cm –1 was observed after NO exposure and was irreversible after purging with N 2 . This band was assigned to NO binding to Cu centers or NO reacting with organic protons of the framework to form R-NO nitroso compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Isolation of L ′ followed by spectral characterization confirmed the C-nitrosation unambiguously (Experimental Section). It is to be noted that the aromatic C-nitrosation in the reaction of Cu­(II) complexes with NO was observed earlier only in one case, although there are a number of examples of the N-nitrosation. ,, The formation of the C-nitrosated ligand can be envisaged considering the reduction of Cu­(II) center by NO leading to the simultaneous formation of NO + , which is very reactive and unstable . This then reacted with the phenol ring to afford C-nitrosation.…”
Section: Resultsmentioning
confidence: 99%
“…In our study on the reactivity of NO with Cu­(II) complexes, it has been observed that the reduction of Cu­(II) center by NO resulted in the aromatic C-nitrosation. For example, when the Cu­(II) complex of 4-amino-3-hydroxynaphthalene-1-sulfonic acid was treated with NO in acetonitrile solution, the reduction of the metal center was observed with concomitant C-nitrosation of the phenol ring present in the ligand framework . This reaction is more like the examples of N-nitrosation of the ligand frameworks in the reaction of Cu­(II) complexes with NO (Scheme ).…”
Section: Introductionmentioning
confidence: 92%
“…It was not possible at the time to determine whether the metal atom coordinated to the nitrogen or the oxygen atom of the nitroso group. It has now been confirmed using single crystal X-ray diffraction (XRD) analysis that coordination is through the nitrogen (Figure 4) [29,48]. A Jahn-Teller distorted octahedral geometry is adopted, with the two aromatic ligands forming an equatorial plane and the axial positions occupied due to oligomerisation, with the phenolic oxygen typically as the donor, although its distance is a little outside the primary coordination sphere of the copper and instead within the Van der Waal’s radii [49].…”
Section: Introduction To Metal-nitrosophenolato Complexesmentioning
confidence: 99%